A General-Purpose Web-based TOPSIS tool for Accessible Multi-Criteria Decision Making - Bata, Julius Victor Manuel (Jurnal Teknik Informatika (Jutif), 2025)
Multi-Criteria Decision Making (MCDM) is a crucial framework for evaluating alternatives based on diverse and often conflicting criteria. However, most existing MCDM tools still require technical skills or software installation, which limits their accessibility for non-technical users. This study introduces Topsisku, a general-purpose web-based decision support system that implements the TOPSIS method. Topsisku enables users to upload datasets, assign weights and criterion types, and obtain ranking results directly through an intuitive web interface. The system was evaluated using three case studies from prior literature, each representing a different domain. Results indicate that the system’s computations are identical to manual calculations, with Spearman rank correlation coefficients approaching perfection (ρ ≈ 1.0; p < 0.001). A usability test involving 10 respondents yielded an average System Usability Scale (SUS) score of 76.5, placing Topsisku in the Good usability category. These findings confirm that Topsisku is both mathematically accurate and user-friendly. The primary contribution of this study lies in democratizing the application of MCDM for non-technical users while maintaining the reliability of the TOPSIS method. Future research directions include the development of advanced sensitivity analysis modules, integration of collaborative multi-user features, and the incorporation of artificial intelligence techniques to enhance system adaptability and decision-making support.